Circulating naïve and effector memory T cells correlate with prognosis in head and neck squamous cell carcinoma. Issue 1 (16th November 2021) - Takahashi, Hideyuki; Sakakura, Koichi; Ida, Shota; Kawabata‐Iwakawa, Reika; Matsuyama, Toshiyuki; Tada, Hiroe; Mito, Ikko; Chikamatsu, Kazuaki
Abstract: T‐cell memory is an important mechanism for long‐term protection against diverse pathogens. Generation and persistence of memory T cells are vital components of anti‐tumor immunity, given their ability to persist for prolonged durations, as well as activate and migrate rapidly. In the present study, we investigated the clinical and prognostic significance of T‐cell subsets in the peripheral circulation of patients with head and neck squamous cell carcinoma (HNSCC). Moreover, we calculated the enrichment scores of T‐cell subsets in primary tumor tissues and compared their clinical characteristics using a public database. Multivariate survival analyses of circulating T‐cell parameters revealed that clinical parameters, except M factor, were not independent prognostic factors, whereas proportions of CD8 + T cells, naïve T cells (TN s), effector memory T cells (TEM s), and CD38 + CD8 + T cells were independent prognostic factors, suggesting the importance of these peripheral T‐cell parameters as independent prognostic biomarkers. Consistent with these results, the T‐cell enrichment analysis indicated that enrichment of CD8 + TN s in the tumor microenvironment was an independent prognostic factor. Moreover, an ex vivo experiment demonstrated significantly less cytotoxic activity in CD38 + T cells than in CD38 − T cells. These findings suggest that T‐cell memory‐related parameters in both systemic immunity and the tumor microenvironment could be used as prognostic biomarkers regardless of clinical characteristics. Further characterization of circulating T cells would lead to the development of novel biomarkers for patients with HNSCC. Abstract : This study demonstrated that the proportion of circulating CD8 + T cells, naïve T cells, and effector memory T cells were independent prognostic factors in patients with HNSCC. Moreover, CD38 expression on circulating T cells correlated with an unfavorable prognosis.